Modeling and simulation of iron/sand filters - Kamga, Fulbert; Noubactep, Chicgoua; Woafo, Paul (Revue des sciences de l’eau / Journal of Water Science, 2012)
Water pollution is increasingly becoming an issue of global concern, especially in developing countries. Therefore, the development of affordable, reliable, low-maintenance, electricity-free technologies for reducing biological and chemical pollutants in drinking water to an acceptable level for human consumption is an interesting topic of research. The suitability of metallic iron (Fe0) as a universal filter material has been recently discussed. Iron/sand filters have a great potential for rural regions where source water may be subjected to various microbial and chemical contaminations. This is based on the fact that corroding iron has the ability to remove all soluble species by an unspecific mechanism. This article develops a mathematical model of iron(Fe0)/sand filter taking into account the loss of porosity during the filtration process. The porosity loss with time is calculated using the rate of formation of corrosion products. The time after which the porosity is reduced to zero indicating a zero flow rate is estimated. The mass transport advection-dispersion equation is derived to predict, through numerical simulation, the spatiotemporal distribution of pollutants and the flow rate in the filter as well as the water quality at the exit of the filter. The control parameters are the iron proportion, the volume of sand particles, the height of the filter and the sorption coefficient. It is found that the pollutant removal percentage and the service life of the filter depend on the relative proportions of sand and iron in the filter.For instance, taking the guideline equal to be 25% of the influent concentration, simulation results demonstrated that by mixing sand and iron particles in proportion of 40 vol% Fe0, the filter can be used continuously for 83 months.